Effect of multi-angle diesel injector nozzle on emission and efficiency of natural gas/diesel dual-fuel combustion in compression ignition engine. (15th May 2022) - Oh, Junho; Oh, Sechul; Kim, Changgi; Lee, Sunyoup; Lee, Seokhwan; Jang, Hyungjun; Lee, Jeongwoo
Highlights: Effects of multi-angle injector on DF combustion was evaluated. Multi-angle injector helped to reduce NMHC emissions under RCCI. Multi-angle injector showed better GIE due to lower HT loss. GWI could be improved more by multi-angle injector under RCCI. Abstract: In this study, natural gas and diesel dual-fuel combustion in a heavy-duty compression ignition engine is experimentally evaluated by adopting a modified multi-angle nozzle of a diesel injector to reduce the global warming impact (GWI) factor while maintaining high thermal efficiency. The original injector has a single layer with an umbrella angle of 150° and eight holes, whereas the modified injector has an additional layer below with an injection angle of 90° and four holes. The engine speed is 1, 200 rpm under low load conditions (intake pressure of 0.11 MPa and overall equivalence ratio of 0.5, such that the torque is varied); meanwhile, the natural gas fraction is varied from 45% to 71% while considering the combustion stability. The diesel injection timing is varied from the top dead center to 70° before top dead center at intervals of 10° for the injector nozzle conditions. Results show that the modified injector improves combustion efficiency under the reactivity-controlled compression ignition (RCCI) regime. In addition, the GWI factor is reduced by 5.6% compared with that of the original injector. Hence, RCCI combustion by early diesel injection using a multi-angle nozzle affords low emissions while considering the GWI factor, as well as maintains a high gross indicated thermal efficiency of 48.6%.